Boiler Regulatory System - Wadbudhe, C; Godbole, T; Syeda, R (International Journal of Computer Sciences and Engineering, 2025)
The steel industry is one of the most important industries in India. During 2014 through 2015, India was the third largest producer of raw steel. Analysis of these plants at all times is a must, since these plants are operated continuously. Boiler is the major part of any Steel plant. Hence monitoring the boiler parameters such as temperature and humidity are of great importance in Steel plant. It is not always possible for continuous monitoring in the plant premises because of an unpleasant industrial environment. In this project it is proposed to develop boiler regulatory system. The proposed method provides a solution for these constraints by using an application to analysis the boilers. The proposed method also provides an option of alarm system if boiler exists the maximum temperature.